Four Turkish families with hyperekplexia: A missense mutation and the exon 1–7 deletion in the GLRA1 gene - Tezen, Didem; Şimşir, Gülşah; Çokar, Özlem; Demirbilek, Veysi; Başak, A. Nazlı; Yapıcı, Zuhal (Parkinsonism & related disorders, 2022)
Hyperekplexia is a disease that progresses with excessive startle attacks and is included in the differential diagnosis of epilepsy and many movement disorders. The WES results were validated in available family members by Sanger sequencing, or in the case of deletion, PCR followed by agarose gel electrophoresis was performed. WES analysis revealed the previously reported homozygous c.277C>T p.Arg93Trp variant in the GLRA1 gene (ENST00000455880.2) in Family 1. In all other three families, the previously reported homozygous deletion of exons 1–7 of the GLRA1 gene was identified using CNV analysis based on the WES data. The homozygous exon1-7 deletion has been described several times in different populations and may be a founder mutation in the Kurdish people in Turkey. The family with Arg93Trp variant stems from the Black Sea region of Turkey where close consanguinity is common. These analyses are important to provide genetic counseling to families and for a better understanding of the pathophysiology of the disease. •Drop attacks that can be easily prevented with correct diagnosis.•Recurring and novel mutations in GLRA1.•Genetic counseling for future generations with mutation detection.